From Formality to Substance: Gender-Responsive Budgeting Reform through Village Fiscal Incentives - Firdaus, Firdaus; Andani, Wirda (UIN Sunan Kudus, 2025)
This study examines the low allocation of budgets for women’s empowerment at the village level, which reflects the weak implementation of gender-responsive budgeting in Indonesia. The study focuses on Kubu Raya and Mempawah Regencies in West Kalimantan Province, which were selected because they have adopted performance-based fiscal incentive policies through the Ecology Fiscal Transfer (EFT) scheme. Using a qualitative approach with the Gender Analysis Pathway (GAP), this study analyzes how these policies affect women’s access, control, and benefits in village budget management. Data were obtained from policy documents, village financial reports, and technical assistance results from local governments. The research findings indicate that fiscal incentives encourage increased budget allocations for women’s empowerment and strengthen women’s substantive participation in development planning. However, their effectiveness depends heavily on village institutional capacity and structural support from local governments. This study recommends strengthening the integration of GAP into village planning and budgeting to promote more gender-responsive policy reforms.